THERMAL EFFICIENCY ANALYSIS OF COFFEE BEAN ROASTER BASED ON PARABOLIC DISH COLLECTOR (PDC) WITH THE ADDITION OF FRESNEL GLASS AS A SOLAR RADIATION AMPLIFIER - Muhammad Raihan; Edi Tri Astuti (PT Altin Riset Publishing, 2026)
This study discusses the use of solar energy as a heat source in the roasting process of coffee beans using a Parabolic Dish Collector (PDC), and analyzes the effect of Fresnel glass integration on improving the thermal performance of the system. Field test data collection is carried out repeatedly on two system configurations, namely PDC without and with Fresnel glass. The results showed that in the configuration without Fresnel glass, the temperature of the coffee beans only reached about 200 – 210 °C in the 15th minute, because the heating took place indirectly through the walls of the heating tube. Conversely, with the addition of Fresnel glass, the temperature of the coffee beans reaches the roasting threshold ( 200 °C) faster, namely in the 9th to 10th minute, and increases to 241 – 249 °C in the 12th minute. This shows an acceleration of heating time of about 5 – 6 minutes at the same relatively same intensity of the sun. In addition, the average thermal efficiency of the system increased from 8.36% to 10.60%, or an increase of about 26.9%. This finding proves that the integration of Fresnel glass in PDC is able to accelerate the heating process, increase the working temperature, and improve heat absorption efficiency, so that this technology has the potential to be applied to small-scale coffee roasting processes based on solar energy.